LUSO-BRAZILIAN CASE STUDY ON EXPATRIATION POLICIES AND PRACTICES - Gallon, SHalimar; Fraga, Aline Mendonça; Antunes, Elaine Di Diego (Contextus - Revista Contemporânea de Economia e Gestão, 2019)
Expatriation is a common process in international business, assisting in the interface and alignment of policies and practices of Human Resource Management with the business strategy, and therefore it is highly important in global expansion. This is a qualitative study case with a Brazilian and Portuguese company. The data were collected through semi-structured interviews with 30 interviewed. In addition, the software Max-Qda (2007) was used to assist the organization of categories of analysis based on the content analysis technique. The study shows that there are different policies and practices of expatriation to the surveyed companies influenced by the country context, legislation, strategy and international maturity of the organization and purpose of the expatriation.